Mo Yan’s Symbolism and Literary Root-seeking - Zhang, Hua; Ibrahim, Yosra (Literary Studies, 2022)
Mo Yan is the first Chinese writer to win the Nobel Prize for Literature. After he won the Nobel Prize for Literature in October 2012, he immediately drew the attention of the world. In the past nine years, there have been many theoretical articles on Mo Yan’s creative style and narrative art, but a very few articles on Mo Yan’s root-seeking characteristics from the perspective of symbolism. This paper attempts to explore the ways Mo Yan searches for his roots through his writings.